(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Diabetes Mellitus is a metabolic disorder characterized by hyperglycemia caused by the inability of the pancreas to secrete insulin, impaired insulin action, or both. The management of diabetes mellitus were blood glucose control and improve quality of life. The purpose of this research was to know the correlation correlation blood glucose control with quality of life in diabetes mellitus patient during COVID-19 pandemic. The type of this research was quantitative research with cross sectional approach. The sample were 143 respondents that chased by inclusion criteria used purposive sampling technique. Instrument used questionnaires. The analysis was univariate to know the frequency of distribution and bivariate used chi square test α (0,05). The result showed there was correlation blood glucose control with quality of life in diabetes mellitus patient during COVID-19 pandemic (p value 0,001). Based on the results of the study it’s expected for health services can provided information and identify family support issues, blood glucose control and quality of life with efforts to improved health care in diabetic patients. Therefore, it can improved optimal treatment.